Managing banking relationships - Leahy, Gerald; ScienceDirect eBooks (Cambridge : Woodhead Pub. with the Association of Corporate Treasurers, 1997)
Managing Banking Relationships is the first publication to look at the principles and practice governing relationships between businesses and their bankers. This book examines the services provided by banks to their corporate clients, and looks at the establishment, maintenance, review and, if necessary, termination of the resulting relationships. Managing Banking Relationships shows how to build and maintain effective modern banking relationships which are based on flexability, mutual interest and trust. It presents the key aspects to good relationships that are profitable to both sides and also illustrates how to select a bank and review the subsequent relationship. With contributions from leading figures from the banking and corporate treasury community this book is invaluable to corporate treasurers, finance directors, bankers and the financial advisory community.
European monetary unionWhither banking relationships?; Index.
Print version record.
Elsevier
Keywords: Banks and banking; Corporations -- Finance; BUSINESS & ECONOMICS -- Finance; Banks and banking; Corporations -- Finance; Relatiemarketing; Banken (financiële instellingen); Electronic books